The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jclinepi.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported medication use validated through record linkage to national prescribing data

Abstract: ObjectivesResearchers need to be confident about the reliability of epidemiologic studies that quantify medication use through self-report. Some evidence suggests that psychiatric medications are systemically under-reported. Modern record linkage enables validation of self-report with national prescribing data as gold standard. Here, we investigated the validity of medication self-report for multiple medication types.Study Design and SettingParticipants in the Generation Scotland population-based cohort (N = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 45 publications
7
98
1
2
Order By: Relevance
“…Furthermore, some prior studies relied on self‐reported use, while others had access to computerized pharmacy data. The latter is likely to have greater validity . Another possible explanation could be differences in the ability to control for potential confounding factors, including concomitant medication use, physical activity, smoking, BMI, ADLs or IADLs, gait speed, and exercise (all of which the present study was able to consider).…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, some prior studies relied on self‐reported use, while others had access to computerized pharmacy data. The latter is likely to have greater validity . Another possible explanation could be differences in the ability to control for potential confounding factors, including concomitant medication use, physical activity, smoking, BMI, ADLs or IADLs, gait speed, and exercise (all of which the present study was able to consider).…”
Section: Discussionmentioning
confidence: 82%
“…Self-reported use of prescription tranquilizers is expected to be reliable and valid (Haapea et al, 2010;Hafferty et al, 2018;Rauma et al, 2013). Use of prescription tranquilizer medication was asked in the Tromsø VI (2007-08) questionnaire as: "How often have you used prescription tranquilizers during the last four weeks?"…”
Section: Use Of Prescription Tranquilizers (Tromsø Vi)mentioning
confidence: 99%
“…A total of 267 publications were identified over the period January 2009 to March 2019. After screening titles and abstracts, and removing duplicates and conference abstracts, 40 full publication articles were included and reviewed . The number of articles published by year for the period 2014–2018, totalling 37, is presented in Figure A; a further 3 studies were published in the first months of 2019.…”
Section: Introductionmentioning
confidence: 99%